Simplified numerical method for latticed shells that considers member geometric imperfection and semi-rigid joints. Issue 4 (April 2016) - Zhao, Zhongwei; Chen, Zhihua; Yan, Xiangyu; Xu, Hao; Zhao, Bingzhen
Most finite element models of actual projects established in general finite element software are rigidly connected or connected by hinge joints. Member imperfection cannot be considered in such models, which is inconsistent with the actual situation in most projects. To estimate the influences of joint stiffness and member imperfection on the mechanical behavior of latticed shell structures, double elements and imperfect members were combined in this study. First, the accuracies of double elements and imperfect members were validated. Then, they were combined to establish imperfect elements with semi-rigid joints. The accuracy of imperfect elements with semi-rigid joints was also validated, and the relationship between joint stiffness and that of double elements was deduced. The findings validated that imperfect elements with semi-rigid joints could consider semi-rigid joints and imperfect members simultaneously and with high accuracy. In addition, imperfect elements with semi-rigid joints could be constructed conveniently in general finite element software.